Analysis of Child Marriage Prevention in Sidoarjo Regency - Sukmana, Hendra; Suhartini, Dian (Universitas Muhammadiyah Sidoarjo, 2019)
Writer 's it aims to analyze and describe the strategies an obstacle Strategies Prevention of Marriage Children in the District of Sidoarjo . Writer 's is based on a fact that child marriages still occur in age or mentality of the child's thought patterns that are caused due to the circumstances pregnant at the outside of marriage on children that are into a problem which should be in preventing the marriage of children . Methods The author 's is using descriptive qualitative , techniques of collecting the data is done with interviews in depth , observation and study of literature that is relevant . The technique of determining the informants used purposive sampling. The informant in the Writer 's this is the Head of the Protection of Women's Rights and Protection , Head of Fulfillment Rights of the Child , Head of Security Family & Community Engagement , Head of Processing Data Population at the Department P3AKB, Ket ua Children's Forum and Actors Marriage Children in the District of Sidoarjo . Mechanical analysis of the author 's of this is the type of analysis of qualitative Referring to the theory of Miles and Huberman. The author 's results show that , prevention of child marriage is successful , as evidenced by the programs that run on the prevention of child marriage so that the number of child marriages in Sidoarjo can be reduced, in the absence of a culture of